HUBUNGAN MOTIVASI IBU DALAM MELAKUKAN PIJAT BAYI DENGAN KENAIKAN BERAT BADAN BAYI - Sab’ngatun; Sulistiani, Ardiani (Jurnal Kebidanan, 2023)
ABSTRACT Background: Baby massage is an expression of affection between parents and their children, which has an impact on the growth and development of children. Parents who are motivated so that the baby’s growth and development is perfect will be encouraged to do baby massage. It is hoped that the parents after the baby massage will feel comfortable, sleep well, suckle firmly and the baby will gain weight. The purpose of this study was to determine the relationship between mother’s motivation in doing baby massage and baby’s weight gain. Research Method: this research is a correlational analytic study with a cross-sectional approach, the sample in this study were mothers who came to massage their children who came to the Dzaky Spa Musuk Boyolali clinic in March 2023 with a total of 60 respondents. Collecting data with primary data is by distributing questionnaires and secondary data. Univariate data analysis using frequency distribution and bivariate analysis using chi square. Results: From this study, the majority of respondents aged 31-40 years were 31 respondents (51.7%), the majority of secondary education were 25 respondents (41.7%) and the majority worked in the private sector as many as 26 respondents (43.3%). Majority of respondents had strong motivation (49 respondents (81.7%) and the majority had weight gain of 49 respondents (81.7) and the statistical test results obtained a p value of 0.0005 meaning that there is a relationship between the motivation of mothers to do baby massage with weight gain baby. Conclusion: there is a relationship between the motivation of mothers to do baby massage with the baby’s weight gain. Suggestion: providing input to parents to add insight about baby massage so they can do baby massage themselves Keywords: motivation, baby massage, increase, baby’s weight